2017
DOI: 10.1007/s40309-017-0128-2
|View full text |Cite
|
Sign up to set email alerts
|

Envisioning future innovative experimental ecosystems through the foresight approach. Case: Design Factory

Abstract: Change makers are visionaries who wish to bring change to their respective fields. As technological change is accelerating, it is relevant to consider, how the way and what we teach can evolve with the future to remain meaningful and pioneering. Design Factory at Aalto University, as an innovative experimental ecosystem with interdisciplinary principles and new teaching methodologies has been successful in and at the forefront in educating the students to be change-makers. The paper presents a case study of ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 14 publications
0
6
0
2
Order By: Relevance
“…This study has identified topics in visions on desirable and sustainable futures, which were authored by citizens in connection to three European projects: Civisti, Casi and Cimulact. Involving citizens in such foresight provides a parallel and analogous procedure to expert envisioning [14] and could be further institutionalised to an established form of foresight [2]. The benefits of considering participatory processes in backcasting exercises such as those performed in the examined projects have been observed before [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study has identified topics in visions on desirable and sustainable futures, which were authored by citizens in connection to three European projects: Civisti, Casi and Cimulact. Involving citizens in such foresight provides a parallel and analogous procedure to expert envisioning [14] and could be further institutionalised to an established form of foresight [2]. The benefits of considering participatory processes in backcasting exercises such as those performed in the examined projects have been observed before [19].…”
Section: Discussionmentioning
confidence: 99%
“…Addressing citizens as contributing foresight actors provides a largely untapped resource for foresight studies. Accordingly, developing and institutionalising procedures for citizen involvement in foresight [14,15] would help scholars to find their way amongst the myriad of methodologies and aims [16,17]. Apart from helping to overcome problems accrued from a democratic deficit in foresight due to heavy reliance on experts, citizen involvement may also reveal knowledge that experts do not identify as relevant or value highly [1].…”
Section: Citizen Involvement For Sustainable Futuresmentioning
confidence: 99%
“…Collaboration with external actors and the innovation ecosystem for the integrated development of innovations and technologies is a theme widely debated by studies on OI (e.g., Van de Vrande et al, 2009;Huizingh, 2011;Munigala et al, 2018;Pitelis & Teece, 2018). In this sense, as observed by Holzmann et al (2014), a fundamental activity in OI is to find suitable partners for collaboration.…”
Section: Open Innovationmentioning
confidence: 99%
“…The work of Munigala, Oinonen and Ekman (2018) analyzes the success of the Finnish educational system from a case on the perspective of the design of innovative environments that allow people to be agents of change (the students in that case), this, through the generation of scenarios that enable the resolution of problems from a holistic, personalized, flexible and collaborative perspective.…”
Section: Theoretical-conceptual Reviewmentioning
confidence: 99%